2010
DOI: 10.1007/s00011-010-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HSP70 on the compression force-induced TNF-α and RANKL expression in human periodontal ligament cells

Abstract: These results indicate that HSP70 may modulate the mRNA expression of TNF-α and RANKL in hPDL cells in response to CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
1
17
1
Order By: Relevance
“…These data indicate that marsupialization may affect the OPG/RANK/RANKL signaling pathway. Considering that the high pressure within the cyst cavity may induce RANKL expression and result in the formation of osteoclasts, we speculated that the effect of marsupialization on the OPG/RANK/RANKL signaling pathway may be due to the release of intracystic pressure (26,27). In addition, marsupialization might induce inflammation and eliminate the possibly hypoxic environment of the cavity (8,28), affecting activation of the OPG/RANK/RANKL signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that marsupialization may affect the OPG/RANK/RANKL signaling pathway. Considering that the high pressure within the cyst cavity may induce RANKL expression and result in the formation of osteoclasts, we speculated that the effect of marsupialization on the OPG/RANK/RANKL signaling pathway may be due to the release of intracystic pressure (26,27). In addition, marsupialization might induce inflammation and eliminate the possibly hypoxic environment of the cavity (8,28), affecting activation of the OPG/RANK/RANKL signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 9 is the mediator of the intrinsic pathway, and an alteration in oxidative phosphorylation, hypoxia and oxidative stress can induce the activation of caspase 9 12) . We previously studied the mRNA expression of TNF-and found that it increased significantly 21) . We therefore hypothesize that the mechanism of apoptosis through caspase 8 activation is mediated by TNF-.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the increased expressions of cytokines and chemokines during experimental tooth movement because of the application of heavy force (50 g) in vivo and the effects of compression forces (0-4.0 g/cm 2 ) in vitro 17,21) . The highest amount of cell damage was 16.9% in the compression force (4.0 g) group 21) . It is difficult to determine the optimal force during therapeutic orthodontic tooth movement, because periodontal tissue reactions vary among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be caused by the up-regulation of VEGF in that it could partially act as a macrophage colony-stimulating factor, 21 and the RANKL expression in OBs induced by COX-2(PGE 2 )/IL-1. 26,27 However, compression and hypoxia act in a magnitude-dependent manner, 29,30 while the adopted interventions in the present study (compression of 25 g/cm 2 and 2% O 2 ) may not be proportional to the in vivo environment, which should be further clarified.…”
Section: Discussionmentioning
confidence: 81%